A Jurisprudential and Legal Study of the Effect of Termination Compared to Previous Contracts - Mahdi Chegeni; Saeed Siah Bidi Kermanshahi (آموزه‌‌های فقه مدني, 2020)
Traditionally, one of the distinguishing features of termination and annulment of a contract is considered to be that annulment makes the contract ineffective from the beginning, and termination has no effect on the past and makes the contract ineffective for the future; but the problem is that in Imamiyyah jurisprudence and current law, the issue of the ineffectiveness of the contract is a rule compared to the past and can be cited in many cases or not? And if there is such a rule, what are the exceptions to that rule? The present jurisprudential and legal article shows that contrary to the law of countries such as France and Egypt, in which termination has a regressive effect, in our legal system, as a rule, it can be said that the termination term refers to the future and is ineffectual to the previous contracts; however, this rule, like many other rules, is not immune from particularization, and in many cases, such as subordinate contracts, secondary contracts, some businessmen transactions after the conclusion of the composition contract, as well as transactions following the conditional (optional) sale, the termination of the main contract compared to contracts which concluded after the main contract and before termination have an effect and, as the case may be, cause the dissolution, invalidity or annulment of the mentioned contracts.